1996
DOI: 10.1046/j.1365-313x.1996.09040505.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a carotenoid biosynthesis gene promoter during plant development

Abstract: Carotenoids are terpenoid pigments which are accumulated in the chloroplasts of leaves and in the chromoplasts of many flowers and fruits. Phytoene desaturase (Pds), the second dedicated enzyme in carotenoid biosynthesis, is encoded in tomato by a single copy gene. A 2 kb fragment from the tomato Pds gene, comprising 1.5 kb from the promoter and 0.5 kb from the 5' non-translated region, is able to drive developmentally regulated expression of the GUS reporter gene in transgenic tomato and tobacco plants. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 0 publications
9
74
1
1
Order By: Relevance
“…ZDS and bLCY) and upstream (IPI, GGPS and PSY) pathway genes were downregulated, but also those related to the biosynthesis of gibberellins as well as chlorophylls (Qin et al 2007). The absence of downstream carotenoids in pds3 mutants could provide the signal as evidence from the analysis of a tomato PDS promoter::GUS fusion demonstrated end product regulation in photosynthetic tissues (Corona et al 1996). OsPSY3 gene expression is upregulated in rice during increased abscisic acid (ABA) formation as well as upon salt treatment and drought, especially in roots indicating that the third PSY allele in rice plays a specialised role in abiotic stress-induced ABA formation (Welsch et al 2008).…”
Section: Carotenoid Signals and Metabolite Feedback Controlmentioning
confidence: 99%
“…ZDS and bLCY) and upstream (IPI, GGPS and PSY) pathway genes were downregulated, but also those related to the biosynthesis of gibberellins as well as chlorophylls (Qin et al 2007). The absence of downstream carotenoids in pds3 mutants could provide the signal as evidence from the analysis of a tomato PDS promoter::GUS fusion demonstrated end product regulation in photosynthetic tissues (Corona et al 1996). OsPSY3 gene expression is upregulated in rice during increased abscisic acid (ABA) formation as well as upon salt treatment and drought, especially in roots indicating that the third PSY allele in rice plays a specialised role in abiotic stress-induced ABA formation (Welsch et al 2008).…”
Section: Carotenoid Signals and Metabolite Feedback Controlmentioning
confidence: 99%
“…In fact, early phases of normal chloroplast formation are characterized by upregulation of carotenoid biosynthesis (Corona et al, 1996) to cover the need for de novo photosystem assembly and for protection against photooxidation (which could occur in partially assembled photosystems and/or because of the presence of photoreactive chlorophyll biosynthesis intermediates). Furthermore, during these stages, the presence of IM may be crucial because the IM-independent phytoene desaturation pathway (photosynthetic electron transfer chain) may not be fully functional.…”
Section: Molecular and Physiological Basis For The Variegated Phenotypementioning
confidence: 99%
“…However, mutations in the gene encoding the phytoene desaturase itself (designated PDS3) [14] have not been reported. Expression analysis of the gene (PDS3) encoding the phytoene desaturase indicated that it is highly regulated by light [18,19] in tomato. Nevertheless, analysis of the immutans mutant showed that the expression of PDS3 gene was not necessarily correlated to the amount of pigments in the cells [20].…”
Section: Introductionmentioning
confidence: 99%